This is PR the realities of public relations - Newsom, Doug (Wadsworth series in mass communication and journalism., 2013)
"Ideal for the beginning student or the experienced public relations practitioner, This is PR: The realities of public relations, Eleventh Edition, covers the world of public relations with a strong emphasis on fundamentals such as history and research, as well as emerging issues such as technology, ethics, and the international aspects. With numerous examples, strategies, tactics, and case studies, you'll have resources you can take away from the classroom."--Publisher's website.